2022
DOI: 10.3390/audiolres12060066
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Cochlear Nerve Function Monitoring in Hearing Preservation Surgery: A Systematic Review of the Literature

Abstract: With the recent scientific and technical developments, hearing preservation surgery is becoming a growing objective in inner ear pathologies, especially for vestibular schwannomas. In this review, we aim to describe the pros and cons of the following cochlear nerve monitoring techniques: ABRs (auditory brainstem responses), DENM (direct eighth cranial nerve monitoring), EcochG (electrocochleography), CNAP (cochlear compound nerve action potentials), DPOAE (distortion product otoacoustic emissions), PAMRs (post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Most clinical neuroelectrophysiologists involved in BAEPs monitoring during CPA operations consider V-wave latency and amplitude as optimal electrophysiological indicators indicative of cochlear nerve injury caused by the operation 27 . However, previous studies have demonstrated that that these raw indicators lack reliability, a concern also reflected in our analysis findings 9 . Comparing pre- and post-resection raw BAEPs analysis results revealed that neither Am-V nor La-V can serve as consistent predictors of HP simultaneously, with both exhibiting an AUC value below 0.7.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Most clinical neuroelectrophysiologists involved in BAEPs monitoring during CPA operations consider V-wave latency and amplitude as optimal electrophysiological indicators indicative of cochlear nerve injury caused by the operation 27 . However, previous studies have demonstrated that that these raw indicators lack reliability, a concern also reflected in our analysis findings 9 . Comparing pre- and post-resection raw BAEPs analysis results revealed that neither Am-V nor La-V can serve as consistent predictors of HP simultaneously, with both exhibiting an AUC value below 0.7.…”
Section: Discussionmentioning
confidence: 61%
“…Methods traditionally used for intraoperative cochlear nerve monitoring include brainstem auditory evoked potential (BAEPs), cochlear nerve action potential (CNAP), and transotympanic electrocochleography (TT-ECochG) 9 . CNAP can realize continuous real-time monitoring of cochlear nerve function during surgery, but it requires clear anatomical positioning of cochlear nerve and space for placing electrodes, so it is mostly used for VSs with small tumor size (< 1.5 cm) 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different techniques have been proposed to monitor the nerve during surgery, i.e., Auditory Brainstem Responses (ABR), Direct Eighth Cranial Nerve Monitoring, Cochlear Compound Nerve Action Potentials (CNAP), Transtympanic Electrocochleography, Distortion Product Otoacoustic Emissions, Postauricular Muscle Responses. All of them may play a role in hearing preservation, but literature is lacking standardized studies, necessary for evaluating their true efficacy, determine the best one for each situation and understand their predictive role for HPS, as a recent review concluded [ 48 ]. To date, the choice of the correct method for monitoring the cochlear nerve is left to surgeons and should be based on the characteristics of the tumor, the patient, and the surgery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported irreversible hearing loss in these patients, even during observation [ 43 ]. Ariano et al, in their review, mentioned that the growing objective of surgical resection of VS is hearing preservation, with retrosigmoid and middle fossa approaches becoming more popular as they are associated with hearing preservation [ 44 ]. Surgical resection is recommended for large tumors causing brain stem compression, especially in young patients.…”
Section: Discussionmentioning
confidence: 99%